Short Communications Caring for Muslim Patients - Some Religious Issues - AK, Iftikhar; IP, Parvez (IIUM Medical Journal Malaysia, 2009)
Islam is a universal religion and a comprehensive way of life that cannot be separated from patients. Muslim patients are not just passive recipients of medical decisions, but have their own religious views and beliefs about how they would like to be cared for by the medical profession. With the increasing Muslim population in the west, problems arise when a Muslim patient is admitted to a hospital with non-Muslim health caregiver, particularly related to dietary and nutritional issues. The health team should be aware of the religious prohibitions in Islam such as wine or alcohol, flesh of swine, reptiles, birds with talons, canine animals or scavenging creatures, intoxicants etc. The guidelines presented in this paper would enable the health provider to serve their Muslim patients in the most appropriate manner.